Phytochemical characterisation of a cytotoxic stem bark extract of Steganotaenia araliacea and identification of a protoflavanone by LC–SPE–NMR. (June 2015) - I. Rica Capistrano,; Wouters, An; Foubert, Kenn; Baldé, Aliou M.; Apers, Sandra; Lardon, Filip; Pieters, Luc; Exarchou, Vassiliki
Graphical abstract: Highlights: Cytotoxicity of Steganotaenia araliacea extract against several cancer cell lines. Identification of spiropreussomerin A and the flavanonol conrauiflavonol/afzelin A. Identification of a novel protoflavonoid steganoprotoflavanone. Abstract: A 80% ethanolic stem bark extract of Steganotaenia araliacea (Apiaceae) showed cytotoxic properties against MDA-MB-231 (breast), PANC-1 (pancreas) and HT-29 (colon) cancer cell lines. Phytochemical investigations by LC-SPE-NMR led to the identification of spiropreussomerin A, most probably produced by an endophytic fungus, the flavanonol conrauiflavonol / afzelin A, and a protoflavanone that has not been reported before and for which the name steganoprotoflavanone was adopted. Surprisingly none of the previously reported cytotoxic dibenzocyclo-octadiene lactone lignans was obtained as a major constituent of the cytotoxic extract.